2018
DOI: 10.14483/2256201x.12604
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de cuatro métodos de evaluación visual del riesgo de árboles urbanos

Abstract: Cuatro métodos de evaluación visual del riesgo se aplicaron en 30 árboles urbanos con niveles de riesgo en la ciudad de Talca (Chile). Los métodos utilizados fueron: “Avaliação de árvores de risco na arborização de vias públicas de Nova Olímpia” (método Sampaio), “Internation Society of Arboriculture (ISA) Matheny y Clark” (método ISA[A]), “Best Management Practice BMP/ISA” (método ISA[B]) y “Urban tree risk management USDA Forest Service” (método USF). Los resultados fueron estandarizados para su análisis est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Visual assessment methods are recognized as efficient for determining the probable risk of rupture of urban trees. Reyes de la Barra et al (2018), comparing four methods of visual risk assessment of urban tree fall, found that visual tree assessment appears to be a reliable tool for predicting tree damage or deterioration and an effective alternative for tree risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Visual assessment methods are recognized as efficient for determining the probable risk of rupture of urban trees. Reyes de la Barra et al (2018), comparing four methods of visual risk assessment of urban tree fall, found that visual tree assessment appears to be a reliable tool for predicting tree damage or deterioration and an effective alternative for tree risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…All of the basic visual tree failure assessment methods in common use today are qualitative in nature [47]. However, using various visual assessment methods to compare tree failure results, significant differences were found between them [48]. Therefore, although existing methods can play a role in rapid, large-scale urban tree failure assessment, they rely too much on the knowledge of tree professionals in the assessment process, resulting in a certain amount of subjectivity and uncertainty in the final assessment results [26,49].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the assessment Level 2, there are different methods, where each proposal seeks to give an approach that best fits the needs of the context where it is applied (Calaza and Iglesias 2016, Reyes et al 2018, Coelho-Duarte et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies in Latin America with the eva-luation of the adherence, adaptation or development of a method applicable to a particular condition (be it territorial or managerial) as objectives. Some are aimed at proposing context-specific methodologies (Sampaio et al 2010, Conceição et al 2017, while others compare existing methods and propose their adjustment (Reyes et al 2018, Ivasko et al 2019, without consistent results to recommend a specific method.…”
Section: Introductionmentioning
confidence: 99%